Efektifitas Berbagai Konsentrasi Rebusan Akar Wangi (Vetiveria zizanoides) terhadap Daya Hambat Bakteri Streptococcus mutans - Surati Surati; Betty Saptiwi (Jurnal LINK, 2015)
Purpose of this study was to determine the effectiveness of various concentrations of detection of vetiver to the inhibition of bacteria Streptococcus mutans. Type of experimental research, research design completely randomized design (CRD) with free variables stew vetiver with 20,40,60,80 and 100% concentration, with two repetitions. The average power resistor which is a clear area around the disk is measured horizontally, vertically, diagonally diagonal 1 and 2 is 20% (3.25), 40% (4.30), 60% (5.39), 80% (6.39) and 100% (7.81). One way ANOVA test results obtained significant value. Results of the Tukey post hoc test showed that stew vetiver has given inhibitory effect (clear zone) against Streptococcus mutans bacteria. Decoction of vetiver (Vetiveria zizanoides) can inhibit the Streptococcus mutans bacteria and the inhibition of bacterial growth sterptococcus mutans tends to increase with increasing concentration of decoction of vetiver (Vetiveria zizanoides).